Gross Motor Function Measure‐66 trajectories in children recovering after severe acquired brain injury. (29th September 2014) - Kelly, Gemma; Mobbs, Sue; Pritkin, Joshua N; Mayston, Margaret; Mather, Michael; Rosenbaum, Peter; Henderson, Robin; Forsyth, Rob
<x xml:space="preserve">Abstract</x> Aim To explore the appropriateness of using the interval‐scale version of the Gross Motor Function Measure (GMFM‐66) in paediatric acquired brain injury (ABI), and to characterize GMFM‐66 recovery trajectories and factors that affect them. Method An observational study of gross motor recovery trajectories during rehabilitation at a single specialist paediatric in‐patient rehabilitation centre using repeated GMFM‐66 observations. The cohort comprised children rehabilitating after severe ABI of various causes. Results A total of 287 GMFM observations were made on 74 children (45 males, 29 females; age‐at‐injury range 0.3–17.3y, median age 11.3y, interquartile range 6.6–15.0y). Differences in item‐difficulty estimates between this sample and the cerebral palsy population in which the GMFM‐66 was initially developed are not detectable at this sample size. Changes in GMFM over time show lag‐exponential forms. Children sustaining hypoxic–ischaemic injuries made the slowest and least complete recoveries. Older children made faster gross motor recoveries after controlling for aetiology. The time at which gross motor ability began to rise coincided approximately with admission to the rehabilitation facility. Interpretation Aetiology is strongly associated with gross motor recovery after ABI. Younger age at injury was associated with slower recovery. Comparable item‐difficulty scores in this sample and in the cerebral palsy population suggest comparable sequences of gross motor ability reacquisition.